x2

Download as pdf or txt
Download as pdf or txt
You are on page 1of 12

Notes on lecture 5

Jiten Chandra Kalita and Shyamashree Upadhyay

1 Continuity of a function of 2 variables


Definition 1.0.1. Let f : D ⊆ R2 → R be a function of 2 variables. Let
(a, b) ∈ D. We say that f is continuous at (a, b) if lim(x,y)→(a,b) f (x, y) exists
and equals f (a, b). 

Remark 1.0.2. Let f : D ⊆ R2 → R be a function of 2 variables. Let


(a, b) ∈ D. For checking the continuity of f at (a, b), we should first check
whether or not the limit lim(x,y)→(a,b) f (x, y) exists. If the limit doesn’t exist,
then there is no further question about the continuity of f at (a, b). In this case,
we are not going to proceed any further, and we say that f is not continuous at
(a, b).
If the limit lim(x,y)→(a,b) f (x, y) exists, then we should first check whether or not
f (a, b) is well defined. If f (a, b) is not well defined, then there is no further
question about the continuity of f at (a, b). In this case too, we are not going
to proceed any further, and we say that f is not continuous at (a, b).
If f (a, b) is well defined, then we should check whether or not lim(x,y)→(a,b) f (x, y)
equals f (a, b). If it equals f (a, b), then we say that f is continuous at (a, b).
Otherwise, we say that f is not continuous at (a, b).
−y 2 2
Example 1.0.3. Check the continuity of f (x, y) = xx2 +y 2 at (0, 0).

Observe that we had already seen in the previous lecture that

x2 − y 2
lim
(x,y)→(0,0) x2 + y 2

does not exist. So, f is not continuous at (0, 0). Moreover, the function f
here is not well defined at (0, 0). 

1
Example 1.0.4. Recall that previously, we had proved that

3x2 y
lim exists and equals 0.
(x,y)→(0,0) x2 + y 2

3x2 y
But the function x2 +y 2
is not well defined at (0, 0). Now let us take a function
f given by (
3x2 y
when (x, y) 6= (0, 0)
x2 +y 2
f (x, y) =
0 when (x, y) = (0, 0)
We can easily see now that lim(x,y)→(0,0) f (x, y) exists and equals f (0, 0). So
the function f is continuous at (0, 0). 

Remark 1.0.5. One can easily check that polynomial functions of any degree
are always continuous at all points in R2 .

Remark 1.0.6. If we consider a rational function (that is, a quotient of 2


polynomial functions), then it is always continuous at any point in the domain
of definition. The domain of definition of a rational function is R2 \ ZD , where
ZD denotes the set of all zeroes of the polynomial in the denominator.
−y 2 2
Example 1.0.7. The domain of definition of the rational function xx2 +y 2

is R2 \ {(0, 0)}, and this rational function is continuous at every point in


R2 \ {(0, 0)}. 

Definition 1.0.8. Let D ⊆ R2 . If a function f is continuous at all points of


D, then we say that f is continuous on D. 

2 Partial derivatives
2.1 The heat conduction problem
Suppose we have taken a metallic bar and we are interested in the temper-
ature distribution at all points on the metallic bar. See Figure 2.1.1 for an
illustration.
Suppose first we dip the bar in icecold water. Then we take it out after a
while. Then we know that at all points on the bar, the temperature is going
to be 0 degree celcius. Now again, let us impart some temperature (say, 100
degree celcius) at the top of the bar. If we now take a cross section of the bar

2
Figure 2.1.1: A metallic bar

Figure 2.1.2: A cross section of the metallic bar

(by taking a slice through a vertical plane), then the cross section is going
to look like a metallic plate as shown in Figure 2.1.2.
At the top, the temperature is going to be 100 degree celcius, and as you
move from the top to the bottom of this cross section, the temperature is
going to reduce gradually. At the bottom most point, the temperature is
going to be 0 degree celcius.
After a while, the temperature inside the cross-sectional plate is going to set-
tle down and the temperature distribution is going to look as in Figure 2.1.2.

3
The curves shown in Figure 2.1.2 are the isotherms.
From single variable calculus, we know that the derivative is nothing but the
rate of change of something. So whenever we consider a function f of one
independent variable x, we take some increment ∆x and then we take the
ratio ∆f
∆x
for computing the derivative of f . That means, we try to find out
the rate of change of f with respect to the single variable x.
Here, if we want to consider the rate of change of temperature (of the cross-
sectional plate), we must have a direction along which we should consider the
rate of change! For instance, we may consider the rate of change of tempera-
ture along the vertical direction or along the horizontal direction. Earlier, in
single variable calculus, we were having only one direction to be considered
for calculating the rate of change of a function. But here, we have infinitely
many directions along which we can calculate the rate of change. One of
these directions is the vertical direction, and another is the horizontal one.
The vertical direction can be regarded as the direction along the y-axis. And
the horizontal direction can be regarded as the direction along the x-axis.
If we consider the rate of change only along these 2 directions, that is, along
the x and the y axes, then we are going to come up with the concept of the
partial derivative. The rate of change along an arbitrary direction (not just
along the x and the y axes), is going to the called the “directional derivative”,
which we will study later on.

2.2 Partial derivatives - Definition


Let f be a function of two variables x and y. Let (a, b) be a fixed point in
the domain of f . Define a function g1 (x) of the single variable x as follows:

g1 (x) := f (x, b).

Observe here that the y-coordinate of f is kept fixed as b. Then we have

g1 (a + h) − g1 (a) f (a + h, b) − f (a, b)
g10 (a) = lim = lim
h→0 h h→0 h

This last limit limh→0 f (a+h,b)−f


h
(a,b)
is defined as the partial derivative of
f with respect to x at (a, b). It is denoted by fx (a, b).
Basically, although it is an ordinary derivative of the function g1 (x) at a, we
call it a partial derivative because we are actually considering a function of

4
2 variables.
Similarly, if we define a function g2 (y) of the single variable y as

g2 (y) := f (a, y),

then g20 (b) will give us the partial derivative of f with respect to y at
(a, b). It is denoted by fy (a, b). That is, we have

g2 (b + k) − g2 (b) f (a, b + k) − f (a, b)


g20 (b) = lim = lim = fy (a, b).
k→0 k k→0 k
Till now, we were working with a fixed point (a, b) in the domain of f . But
if we want to take a variable point (x, y) in the domain, then we have

f (x + h, y) − f (x, y)
fx (x, y) = lim
h→0 h
and
f (x, y + k) − f (x, y)
fy (x, y) = lim .
k→0 k
Sometimes the symbols ∂f ∂x
and Dx (x, y) are also used to denote fx (x, y).
∂f
Similarly, the symbols ∂y and Dy (x, y) are also used to denote fy (x, y).
Hence to find partial derivative of a function of 2 variables, we have to treat
one among the two variables as a constant, and differentiate with respect to
the other variable.

Example 2.2.1. Let f (x, y) = x4 y 3 + sin xy. Find the partial derivatives of
f.
To find fx , we simply consider the variable y (in f (x, y)) as a constant, and
differentiate with respect to x. Therefore,

fx (x, y) = 4x3 y 3 + y cos xy.

Similarly,
fy (x, y) = 3x4 y 2 + x cos xy.


5
2.3 Geometrical interpretation of partial derivatives
Let f be a function of 2 variables x and y. Let (a, b) be a fixed point in the
domain of f .
To find fx (a, b), we are going to fix b, that is, y = b. Now the equation y = b
represents a vertical plane and this plane cuts the surface corresponding to
the graph of f in a curve (say, C1 ). See Figure 2.3.1 for an illustration.

Figure 2.3.1: The surface z = f (x, y) being cut by the plane y = b

Observe that the equation of the curve C1 is given by z = f (x, b). Figure
2.3.2 gives a magnified view of the phenomenon.
Let g1 (x) = f (x, b). Then we know that

Figure 2.3.2: The curve z = f (x, b)

6
dg1
fx (a, b) = g10 (a) = .
dx |x=a

But we know from single variable calculus that dg 1


dx |x=a
is the slope of the
tangent to the curve C1 at the point (a, c), where c = f (a, b). See Figure 2.3.3
for an illustration.
So geometrically, the partial derivative fx (a, b) of f at the point (a, b)

Figure 2.3.3: The tangent to the curve z = f (x, b)

signifies the slope of the tangent line at the point (a, c) to the curve cut out
by the plane y = b from the surface z = f (x, y), where c = f (a, b).
We can have a similar geometrical interpretation for fy (a, b).

2.4 Notation for partial derivatives


If z = f (x, y), then we write
∂f ∂z
fx (x, y) = fx = (x, y) = = f1 = D1 f = Dx f.
∂x ∂x
Similarly, for fy (x, y) (For fy (x, y), we write f2 and D2 f ).

2.5 Rule for finding partial derivatives


Let z = f (x, y).
• To find fx , regard y as a constant and differentiate f (x, y) with respect
to x.

7
• To find fy , regard x as a constant and differentiate f (x, y) with respect
to y.
Exercise: Find the partial derivatives of the following functions:
(i) f (x, y) = 3x − 2y 4 .
(ii) f (x, y) = xR5 + 3x2 y 2 + 3xy 4 .
x
(iii) f (x, y) = y cos(t2 )dt.

3 Functions of more than 2 variables


Partial derivatives can also be defined for functions of 3 or more variables.
For example, if f is a function of 3 variables x, y and z, then its partial
derivative with respect to x is defined as
f (x + h, y, z) − f (x, y, z)
fx (x, y, z) = lim .
h→0 h
It is found by treating y and z as constant and differentiating f (x, y, z) with
respect to x. If w = f (x, y, z), then fx = ∂w ∂x
can be interpreted as the
rate of change of w with respect to x when y and z are held fixed. But we
can’t interpret it geometrically because the graph of f lies in a 4-dimensional
space.
In general, if u is a function of n variables, say u = f (x1 , . . . , xn ), then its
partial derivative with respect to the i-th variable xi is given by
∂u f (x1 , . . . , xi−1 , xi + h, xi+1 , . . . , xn ) − f (x1 , . . . , xi , . . . , xn )
= lim .
∂xi h→0 h
Observe that here we have all variables (except the i-th variable) fixed.
Let x = (x1 , . . . , xn ) ∈ Rn . Write
x =< x1 , . . . , xn > .
Let eˆ1 , . . . , eˆn denote the unit vectors along the directions x1 , . . . , xn respec-
tively, where eˆi is the vector in Rn having 1 at the i-th position and zeroes
elsewhere. It is now easy to see that
x + heˆi =< x1 , . . . , xi−1 , xi + h, xi+1 , . . . , xn > .
We can then write
∂u f (x + heˆi ) − f (x)
= lim .
∂xi h→0 h

8
4 Higher order partial derivatives
If f is a function of 2 variables x and y, then so are the partial derivatives fx
and fy . So we can consider their partial derivatives (fx )x , (fx )y , (fy )x , (fy )y ,
which are called the second order partial derivatives of f . If z = f (x, y),
then we use the notation:

These are called mixed partial derivatives.


Theorem 4.0.1. Clairaut’s theorem: Suppose f is defined on a disc D
that contains the point (a, b). If the functions fxy and fyx are both continuous
on D, then fxy (a, b) = fyx (a, b).
Remark 4.0.2. Sometimes, directly differentiating a function with respect to
x or y partially may not give you a correct picture. For some particular cases,
we may need to find the partial derivative through the definition given by
f (x + h, y) − f (x, y)
fx = lim .
h→0 h
Similar definition for fy .
Sometimes, we may have to use the following definition (or similar definitions):
fx (x, y + k) − fx (x, y)
(fx )y = lim .
k→0 k

9
Example 4.0.3. Let f (x, y) = x4 y 3 + sin xy. Then

fx = 4x3 y 3 + y cos xy.

fxx = (fx )x = 12x2 y 3 − y 2 sin xy.


and fxy = (fx )y = 12x3 y 2 − xy sin xy + cos xy.
Similarly, we can find fy , fyx and fyy . Clearly for this example, Clairaut’s
theorem holds true.
But Clairaut’s theorem may not hold true in all examples. 

5 Tangent planes
Let f be a function of 2 variables x and y. Let z = f (x, y). Let (x0 , y0 )
be a fixed point in the domain of f . Let z0 = f (x0 , y0 ). Then the surface
corresponding to z = f (x, y) passes through the point P = (x0 , y0 , z0 ). Let
us consider the tangent plane to this surface at the point (x0 , y0 , z0 ).
If we know the direction ratios of the normal (say, ~n =< a, b, c >) at the
point (x0 , y0 , z0 ) to the surface, then we can write down the equation of the
tangent plane to the surface at the point (x0 , y0 , z0 ) as follows:

a(x − x0 ) + b(y − y0 ) + c(z − z0 ) = 0.

If c 6= 0, then the above equation can be rewriiten as

z − z0 = A(x − x0 ) + B(y − y0 ), (∗)

where A = − ac and B = − cb .
Now consider the plane y = y0 . Then this plane y = y0 will cut out a curve
(say, C1 ) from the surface. And then, at the point P = (x0 , y0 , z0 ), we will
have a tangent line (say, T1 ). The partial derivative fx (x0 , y0 ) is going to be
the slope of the tangent line T1 . The equation (∗) along the plane y = y0
reduces to
z − z0 = A(x − x0 ). (∗∗)
Now equation (∗∗) also represents the same tangent line T1 , whose slope is
fx (x0 , y0 ). Hence we have
A = fx (x0 , y0 ).

10
Figure 5.0.1: The tangent lines T1 and T2

Similarly, if we consider the plane x = x0 , then we will get a curve C2 , a


tangent line T2 , and
B = fy (x0 , y0 ).
Figure 5.0.1 explains the phenomenon.
That means, if we want to find out the equation of the tangent plane to the
surface z = f (x, y) at the point (x0 , y0 , z0 ) (where z0 = f (x0 , y0 )), then we
will have to simply find out fx (x0 , y0 ) and fy (x0 , y0 ), and replace A and B
in equation (∗) by fx (x0 , y0 ) and fy (x0 , y0 ) respectively. So the equation
of the tangent plane to the surface z = f (x, y) at the point (x0 , y0 , z0 ) is
given by:
z − z0 = fx (x0 , y0 )(x − x0 ) + fy (x0 , y0 )(y − y0 ). (+)
Example 5.0.1. Write an equation of the tangent plane to the paraboloid
z = 5−2x2 −y 2 at the point P = (1, 1, 2). See Figure 5.0.2 for an illustration.
Here, z = f (x, y), where f (x, y) = 5 − 2x2 − y 2 . Also, (x0 , y0 , z0 ) = (1, 1, 2).
So
fx (1, 1) = −4 and fy (1, 1) = −2.
Plugging all this data in equation (+), we get that the required equation of
the tangent plane is given by
z − 2 = −4(x − 1) + (−2)(y − 1).

11
Figure 5.0.2: Figure for Example 5.0.1

Or in other words,
4x + 2y + z = 8.

Remark 5.0.2. We know that the equation of the tangent plane to the surface
z = f (x, y) at the point (x0 , y0 , z0 ) is given by
z − z0 = fx (x0 , y0 )(x − x0 ) + fy (x0 , y0 )(y − y0 ).
This equation can be rewriiten as
fx (x0 , y0 )(x − x0 ) + fy (x0 , y0 )(y − y0 ) + (−1)(z − z0 ) = 0.
Now, a(x − x0 ) + b(y − y0 ) + c(z − z0 ) = 0 is also the equation of the same
tangent plane, where ~n =< a, b, c > is the normal to the surface at the point
(x0 , y0 , z0 ).
If we compare the above two equations, then we get
< fx (x0 , y0 ), fy (x0 , y0 ), −1 >= λ < a, b, c >
for some scalar λ. This implies that < fx (x0 , y0 ), fy (x0 , y0 ), −1 > is also going
to give us the components of the normal to the surface at the point (x0 , y0 , z0 ).
—————-END——————

12

You might also like